2017
DOI: 10.3201/eid2308.151550
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Death among Children with Pneumonia, Afghanistan

Abstract: In Afghanistan, childhood deaths from pneumonia are high. Among 639 children at 1 hospital, the case-fatality rate was 12.1%, and 46.8% of pneumococcal serotypes detected were covered by the 13-valent vaccine. Most deaths occurred within 2 days of hospitalization; newborns and malnourished children were at risk. Vaccination could reduce pneumonia and deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Feedback from healthcare workers suggested the observed reduction in case fatality in the early conflict period was due to better access to essential medications and supplies, and better support and morale of staff (who were required to reside on campus due to insecurity). (23) Similarly high CFRs were reported from urban hospitals in conflict-affected Liberia (12% in children under 15) [ 30 ], and Afghanistan (12% in children under 5) [ 26 ].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Feedback from healthcare workers suggested the observed reduction in case fatality in the early conflict period was due to better access to essential medications and supplies, and better support and morale of staff (who were required to reside on campus due to insecurity). (23) Similarly high CFRs were reported from urban hospitals in conflict-affected Liberia (12% in children under 15) [ 30 ], and Afghanistan (12% in children under 5) [ 26 ].…”
Section: Resultsmentioning
confidence: 93%
“…Three of these studies reported on risk factors for death, adjusting for a variety of individual and social covariates, finding that mortality was associated with lower household socioeconomic status (eg, maternal education, house structure), malnutrition and other chronic conditions [ 22 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is a risk of a vicious cycle of diarrhoea and malnutrition: repeated attacks of diarrhoea and infections leads to weight loss and compromise a child's nutritional status, which makes the child vulnerable to infections and cause further weight loss, eventually leading to severe malnutrition unless the cycle is stopped [21,22]. Association of malnutrition and respiratory infections in children is well known, and the association increases the risk of death [23,24]. Malnourished children have deranged immune system; therefore, viral and bacterial pathogens can easily cause various infections, including the respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six studies met our selection criteria (online supplemental figure 1). 20–45 All studies were hospital-based and, apart from one case–control study, were prospective or retrospective cohorts (online supplemental table 1). Study recruitment years ranged between 1981 and 2016 and included participants throughout Africa, Asia and South America.…”
Section: Resultsmentioning
confidence: 99%